Discrepancies between mirror data on intra- Community trade: the case of Poland - Markowicz, Iwona; Baran, Paweł (Rozbieżności w handlu wewnątrzwspólnotowym: przypadek Polski, 2020)
The content presented in the article is a continuation of the research on the quality of data concerning intra-Community trade. Several measures used in literature to assess differences between mirror data are presented. The research was inspired by the works by Morgenstern (1963), Federico and Tena (1991), and Ferrantino and Wang (2008). These previous works contain some directions on how Intrastat data should be analysed. Based on this the analysed data on intra-Community trade in goods for 2017. The dynamics of intra-Community trade were also examined. The obtained results can be utilised by practitioners from both the domain of official statistics and the revenue authorities. In the article discrepancies in data on Polish foreign trade are studied in the context of Poland-EU partner country (bilateral relations) and Poland-EU partners (one-to-many relations). The aim of the article is to compare the results of selected literature studies with those obtained on the basis of the analysis of the latest data on intra-Community trade in Poland (mainly in 2017) and EU member states
Econometrics = Ekonometria, 2020, Vol. 24, No. 1, s. 1-11
Keywords: intra-Community trade; official statistics; mirror data; handel wewnątrzunijny; statystyka publiczna; dane lustrzane